(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Certain infectious agents have been identified more frequently in cultures from women who have had a spontaneous pregnancy loss; these include Ureaplasma urealyticum, Mycoplasma hominis, and Chlamydia. Objective:The aim of the study was to evaluate the frequency of Chlamydia trachomatis infection among women who experienced recurrent spontaneous abortion. Methods: A total of 119 women, age ranged from 23.9?28.5 years were enrolled in the current study and were classified into: Group A- Recurrent spontaneous abortion (RSA): n= 62 women, with a mean age of (28.5±0.68); Group B- non- recurrent spontaneous abortion (non-RSA): n= 34 women, with a mean age of (26.4±0.85) and group C- Control (successful pregnancy): n= 23 women, with a mean age of (23.9±0.88). From each patient and control blood and urine samples were collected. Urinalysis test strips including Leukocytes esterase in urine was done, and estimation of IgM levels against Chlamydia trachomatis in sera of patients was done using ELISA method. Results:Based on ELISA screening assay, results showed a significant difference in the level of circulating C.trachomatis specific IgM antibody between group A and group C (p< 0.05) as well as between group B and group C (p< 0.01). Also highly significant positive correlation (r=0.401, p